(Suffering) for the Family The Mediated Structure of Feeling Among the Rural Elderly in Post-Reform China - Wu, Hao (Palgrave Studies in Mediating Kinship, Representation, and Difference, 2025)
XI, 247 p. 5 illus., 4 illus. in color.